"I Feel Your Fear": (Counter)stories of East Asian International Doctoral Students About Awakening, Resistance, and Healing. Issue 1 (3rd April 2023) - Qiu, Tairan; Fu, Shuang; Yeom, Eun Young; Hong, Ji Hyun
ABSTRACT: As an extension of the personal and intellectual conversations that took place in the sister-scholar group consisting of four East Asian international doctoral students from China and South Korea, in this article, we narrate and examine our (counter)stories traversing between different spaces and across time. These narratives center our racial, linguistic, social, and academic experiences and illustrate our processes of awakening, resistance, and collective healing. We used transnationalism and Asian Critical Theory as our theoretical guide, and collaborative autoethnography as our methodology. Through the canvas of (counter)stories, we (a) refuse dominant views and definitions of what it means to be Asian in the United States, (b) resist the simplistic and monolithic ways of understanding our existence and experiences as international students, and (c) challenge the academic community and broader society to develop more complex and critical social praxis regarding race, culture, and relations of power.